Containing illicit flows at African borders: Pitfalls for Europe - Judith Vorrath (Stiftung Wissenschaft und Politik (SWP), 2017)
The recent rise in migration to Europe has put borders and their security back on the political agenda of the European Union and its member states. Alongside stricter control of the Union's external borders, border security also plays a growing role in cooperation with third states. The action plan adopted by European and African heads of state and government at the Valletta summit on migration in November 2015 includes assistance for strengthening national capacities at land, air and sea borders. In particular in the immediate southern neighbourhood, this support is intended to contribute to stemming irregular migration and human smuggling. European programmes to combat illicit flows and organised crime at borders outside the EU have existed for some time, for example to interrupt cocaine smuggling via West Africa. The experience to date reveals potential pitfalls of this approach and underlines the necessity to think beyond technical border management.
Keywords: 320